A comprehensive kinetic model for Cu catalyzed liquid phase glycerol hydrogenolysis - Rajkhowa, Tapas; Marin, Guy B.; Thybaut, Joris W. (Applied catalysis. B, Environmental, 2017)
[Display omitted] •Extended reaction network including main and by-products was experimentally identified.•A comprehensive, elementary kinetic model construction for glycerol hydrogenolysis.•Experimental observations explained through physically significant parameters. Hydrogenolysis of biomass-derived glycerol has been investigated as an alternative route for the production of value-added chemicals, such as 1,2-propanediol, also commonly denoted as propylene glycol (PG). Intrinsic glycerol hydrogenolysis kinetics have been acquired experimentally on a stable, commercial copper-based catalyst in an isothermal trickle-bed reactor at 463–513K, hydrogen pressures from 6.5 to 8MPa and space times (W/FG0) from 25 to 340kgsmol−1 resulting in glycerol/PG conversions from 1 to 75mol%. The selectivity to PG amounts to at least 90%. For a given conversion, the lowest selectivity is observed at the highest temperature. Glycerol is predominantly dehydrated to acetol which is subsequently converted to PG. Co-feeding reaction products, i.e., PG and water, does not affect the rate of glycerol conversion. Additionally, glycerol can lead to minor side reactions forming products such as 1,3-propanediol, ethylene glycol while PG can degrade to ethanol, methanol and propanol. A comprehensive kinetic model accounting not only for the formation of main reaction products but also of side products was constructed. The activation energy of the rate-determining step for glycerol dehydration towards acetol was estimated at 84kJmol−1, exceeding that of the rate-determining step of the consecutive hydrogenation into PG by about 25kJmol−1. The high selectivity towards PG is attributed to (1) the relatively lower surface reaction rates for the parallel and the consecutive side reactions and (2) its low affinity for adsorption on the catalyst surface compared to glycerol at the investigated experimental conditions.